2019
DOI: 10.17533/udea.iee.v37n3e05
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and resilience and their relationship with the use of mobile phone among nursing students

Abstract: Objective. The study sought to explore the relationship between levels of stress and resilience with the use of the mobile phone in nursing students. Methods. Cross-sectional study conducted with 102 nursing students from several Nursing schools in India who were invited to participate in the research. The data were gathered by using the following instruments: Perceived Stress Scale(PSS) by Cohen, The Connor-Davidson Resilience scale (CD-RISC), and Mobile Phone Involvement Questionnaire(MPIQ)by Walsh. Results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
0
19
0
2
Order By: Relevance
“…Individual scores range from 0 to 40, with higher scores indicating higher perceived stress. Scores from 0 to 13, 14 to 26, and 27 to 40 are considered low, moderate, and high levels of perceived stress, respectively [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Individual scores range from 0 to 40, with higher scores indicating higher perceived stress. Scores from 0 to 13, 14 to 26, and 27 to 40 are considered low, moderate, and high levels of perceived stress, respectively [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Perceived stress is the cognitive appraisal of the objective stressors ( Cohen et al, 1983 ; Hewitt et al, 1992 ). Recent studies have found that lower levels of perceived stress are associated with higher resilience ( Sarrionandia et al, 2018 ; Smith et al, 2018 ; Thompson et al, 2018 ; Sahu et al, 2019 ). Moreover, it is well known that stress-related etiology is crucial for understanding somatization (e.g., Hewitt et al, 1992 ; Mischkowski et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…16 Studies have shown that low to moderate levels of resilience among Chinese nursing students 13 ; in addition, students with lower resilience capacity may be more vulnerable to adverse psychological outcomes, such as anxiety and depression. 17,18 However, few studies have characterized the effect of childhood trauma on the development of psychological resilience among nursing students. 11 Moreover, adequate redressal of childhood trauma experienced by nursing students and formulation of support strategies for developing their resilience are key imperatives to strengthen their professional practice.…”
mentioning
confidence: 99%